Abemaciclib sensitizes HPV‐negative cervical cancer to chemotherapy via specifically suppressing CDK4/6‐Rb‐E2F and mTOR pathways. (10th June 2020) - Liu, Yuan; Zhao, Runsheng; Fang, Shanshan; Li, Quan; Jin, Yiqiang; Liu, Bo
ABSTRACT: Cervical cancer is the second most common malignancy in women, and the novel therapeutic treatment is needed. Abemaciclib is a FDA‐approved drug for breast cancer treatment. In this work, we identified that abemaciclib has potent anti‐cervical cancer activity. We demonstrate that abemaciclib is the most effective drug against human papillomavirus (HPV)‐negative cervical cancer cells compared to ribociclib and palbociclib, with its IC50 at nanomolar concentration range. This is achieved by the inhibition of proliferation and induction of apoptosis, through specifically suppressing CDK4/6‐Rb‐E2F and mTOR pathways by abemaciclib in HPV‐negative cervical cancer cells. Of note, the combination of abemaciclib with paclitaxel and cisplatin at sublethal concentration results in much greater efficacy than chemotherapy alone. In addition, we confirm the efficacy of abemaciclib and its combination with paclitaxel or cisplatin at the doses that are not toxic to mice in HPV‐negative cervical cancer xenograft mouse model. Interestingly, we show that abemaciclib and other CDK4/6 inhibitors are not effective in targeting HPV‐positive cervical cancer cells, and this is likely to be associated with the high p16 and low Rb expression in HPV‐positive cervical cancer cells. Our work is the first to provide the preclinical evidence to demonstrate the potential of abemaciclib for the treatment of HPV‐negative cervical cancer. The mechanism analysis highlights the therapeutic value of inhibiting CDK4/6 in HPV‐negative but not HPV‐positive cervical cancer.